What economic effect do mega-events have on host cities and their surroundings? An investigation into the literature surrounding mega-events and the impacts felt by holders of the tournaments. - Chen, Na (2008)
This research project sets out to identify the economic impacts that mega-sporting events can have on host economies. A wide range of different mega-events are discussed, including the Olympic Games, World Cup and Formula One events, with a multitude of academic and news articles sourced to obtain insights into the costs and benefits of such competitions. Using a three-dimensional separation of different economic impacts based on the Matos (2006) holy-trinity of economic growth, infrastructure legacy and image promotion, both positive and negative effects are found for mega-events across a period of 40 years, with individual events shaped by the amount of investment placed in the tournament, their attraction to fans and tourists and the level of political influence affecting the worldwide image of the tournament. Events such as the Munich 1972 Olympics had huge negative initial impacts; however, are redeemed by good management across the following years that attract tourists for years after the event. Comparatively, the introduction of the Bahrain GP in 2004 has had a major impact on the host economy in the last four years, with each race adding more to the economy than the last. Areas explored for this section include the expenditure spent in attracting and preparing for the mega-event to the point of hosting the event and beyond; the funding structure put in place to ensure that sufficient money is available for the hosting of the event; the growth and profit effects of events; tourism, employment and retail consequences; the urban regeneration sparked through the hosting of mega-events; the usage of facilities post event so that they do not become burdensome on their host economies and the television coverage leading to worldwide recognition of the host nation that can impact future tourism opportunities. The study also focuses upon the reliability of economic impact studies, as many may fail to account for all anticipated outcomes, with some limited bias in place relating to the researchers personal opinions. Theoretical and methodological issues of such studies are reviewed, with a range of data analysed to determine if such deficiencies would have a significant influence on the accuracy of such data and hence the confidence placed in it.